Sheet metal forming : process and applications - Altan, Taylan; Tekkaya, A. Erman (ASM International, 2012)
This practical and comprehensive reference gives the latest developments on the design of sheet forming operations, equipment, tooling, and process modeling. Individual chapters cover all major sheet forming processes such as blanking, bending, deep drawing, and more. Process modeling using finite element analysis is described in one chapter and discussed in all appropriate chapters. Other chapters cover sensors and die materials, which are critical for practical sheet forming applications. Other topics include relatively new technologies, such as warm forming of magnesium and aluminum alloys, forming of advanced high-strength steels (AHSS), and hot stamping. Chapters also address special sheet forming operations, like spinning, incremental forming, and mechanical joining, and processes related to sheet forming, such as sheet and tube hydroforming, roll forming, and high-velocity forming.